Placenta-Derived Exosomes as a Modulator in Maternal Immune Tolerance During Pregnancy - Bai, Kunfeng; Li, Xintong; Zhong, Jiangming; Ng, Ernest H. Y.; Yeung, William S.B.; Lee, Cheuk-Lun; Chiu, Philip C. N. (Frontiers in Immunology, 2021)
Exosomes are a subset of extracellular vesicles with an average diameter of ~100nm. They represent a new paradigm in intercellular communication. Exosomes are released by all cells through an endosome-dependent pathway and carry nucleic acids, proteins, lipids, cytokines and metabolites, mirroring the state of the originating cells. The function of exosomes has been implicated in various reproduction processes, such as embryo development, implantation, decidualization and placentation. Placenta-derived exosomes can be detected in the maternal blood as early as 6 weeks after conception and their levels increase with gestational age. Importantly, alternations in the molecular signatures of placenta-derived exosomes are observed in pregnancy-related complications. Thus, these differentially expressed molecules could be the potential biomarkers for diagnosis of the pregnancy-associated diseases. Recent studies have demonstrated that placenta-derived exosomes play a key role in the establishment of maternal immune tolerance, which is critical for a successful pregnancy. To gain a better understanding of the underlying mechanism, we highlighted the advanced studies of placenta-derived exosomes on immune cells in pregnancy.